The Role of Leadership and Organizational Culture in Driving Digital Transformation in indonesia SMEs: A Systematic Literature Review - Gustiawan, Wahyu Dede; Pramana, Andy Chandra; Widyaningrum, Santi; Hermawan, Agus; Handayati, Puji (Universitas Kadiri, 2025)
Digital transformation has become a strategic imperative for small and medium-sized enterprises (SMEs), especially in emerging economies like Indonesia. While much attention has been placed on technology adoption, the internal organizational factors—particularly leadership and culture—remain insufficiently examined, despite their critical role in shaping digital readiness and sustainability. This study aims to systematically investigate how transformational leadership and organizational culture interact to influence digital transformation in Indonesian SMEs. It also explores how dynamic capabilities and contextual conditions contribute to digital maturity and resilience. A systematic literature review (SLR) was conducted based on 48 peer-reviewed articles published between 2018 and 2023 in Scopus Q1/Q2 journals. The articles were selected using keyword combinations related to “digital transformation,” “leadership,” “organizational culture,” “dynamic capability,” “TOE Framework,” “SMEs,” and “Indonesia.” Thematic content analysis was used to extract and synthesize core themes. Four dominant themes emerged: (1) transformational leadership enables digital vision, motivation, and adaptive change; (2) adaptive organizational cultures support innovation and reduce resistance; (3) dynamic capabilities—sensing, seizing, transforming—act as strategic mechanisms; and (4) the Technology–Organization–Environment (TOE) framework provides a useful structure for assessing digital readiness. These factors are interdependent and collectively shape the success of SME digital transformation. The study integrates multiple theoretical perspectives—Transformational Leadership Theory, Organizational Culture Theory, Dynamic Capabilities Theory, and the TOE framework—into a comprehensive model of SME digital transformation. It offers practical guidance for leaders and policymakers to design more holistic and context-sensitive digital strategies that extend beyond mere technology adoption